Streptococcus mutans-derived extracellular matrix in cariogenic oral biofilms - Klein, Marlise I.; Hwang, Geelsu; Santos, Paulo H. S.; Campanella, Osvaldo H.; Koo, Hyun (Frontiers in Cellular and Infection Microbiology, 2015)
Biofilms are highly structured microbial communities that are enmeshed in a self-produced extracellular matrix. Within the complex oral microbiome, Streptococcus mutans is a major producer of extracellular polymeric substances including exopolysaccharides (EPS), eDNA and lipoteichoic acid (LTA). EPS produced by S. mutans-derived exoenzymes promote local accumulation of microbes on the teeth, while forming a spatially heterogeneous and diffusion-limiting matrix that protects embedded bacteria. The EPS-rich matrix provides mechanical stability/cohesiveness and facilitates the creation of highly acidic microenvironments, which are critical for the pathogenesis of dental caries. In parallel, S. mutans also releases eDNA and LTA, which can contribute with matrix development. eDNA enhances EPS (glucan) synthesis locally, increasing the adhesion of S. mutans to saliva-coated apatitic surfaces and the assembly of highly cohesive biofilms. eDNA and other extracellular substances, acting in concert with EPS, may impact the functional properties of the matrix and the virulence of cariogenic biofilms. Enhanced understanding about the assembly principles of the matrix may lead to efficacious approaches to control biofilm-related diseases.